(-3x + 8y) (x - y)

(With Solution)


Sagot :

Answer:

ANSWER

Step-by-step explanation:

(-3x + 8y) (x - y)
= (-3x2 + 8xy + 3xy - 8y2)
= (-3x2 + 11xy - 8y2)

Answer:

[tex]-3x^2+11xy-8y^2[/tex]

Step-by-step explanation:

Use the FOIL method

F - means First term

[tex](-3x)(x)=-3x^2[/tex]

OI - means Outer and Inner term

O [tex]= (-3x)(-y)=3xy[/tex]

I [tex]= (8y)(x)=8xy\\[/tex]

Then combine

[tex]3xy+8xy=11xy[/tex]

L - means Last term

[tex](8y)(-y)=-8y^2[/tex]

Lastly, combine all the terms

[tex]-3x^2+11xy-8y^2[/tex]